Prikazi bolesti u romanu Schornstein Jana Faktora i Terminifera Michaela Stavariča - CORNEJO, Renata (Anafora, 2023)
The article deals with the concept of clinical pictures in the prose works Schornstein (2006) by Jan Faktor and Terminifera (2007) by Michael Stavarič. The texts are analysed with regard to the mechanisms of exclusion that contribute to the marginalization and increasing “pathologization” of both main characters. The focus is on the question of how the perception of the main characters by the outside world affects their self-perception and actions. Last but not least, consideration is given to the extent to which the clinical pictures outlined here can be read as a parable or an image of the “illnesses” of our world today.